1995
DOI: 10.1177/096032719501401205
|View full text |Cite
|
Sign up to set email alerts
|

The preclinical toxicological evaluation of sumatriptan

Abstract: 1 Sumatriptan is a potent and selective 5-HT1 receptor agonist marketed for the treatment of migraine by both oral and subcutaneous routes. An extensive toxicologi cal programme employing high doses of sumatriptan was carried out in a range of animal species. The stud ies evaluated both the local and systemic tolerance to single and repeated dosing, effects on all stages of repro duction, as well as the genotoxic and oncogenic poten tial of sumatriptan. 2 The adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…14 There are some studies about the toxicity of this drug just in animals. 3 Our case supports the novel complications of sumatriptan toxicity in humans, including urine incontinency, nephritic syndrome, and hepatotoxicity. Further clinical trials are required to reveal the complications of the sumatriptan, especially in patients with positive past medical history.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…14 There are some studies about the toxicity of this drug just in animals. 3 Our case supports the novel complications of sumatriptan toxicity in humans, including urine incontinency, nephritic syndrome, and hepatotoxicity. Further clinical trials are required to reveal the complications of the sumatriptan, especially in patients with positive past medical history.…”
Section: Discussionsupporting
confidence: 74%
“…Persistent to our study, Owen et al demonstrated tachycardia induced by sumatriptan in animals as well. 3 Some of these complications are related to serotonin syndrome, a drug-induced syndrome associated with sumatriptan administration. 8 This effective drug has major adverse effects such as hepatotoxicity by causing oxidative stress in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[39] However, no mutagenic nitroso compounds were detected following in vitro nitrosation of sumatriptan, a synthetic indole derivative. [40] The evidence that endogenously formed Nnitroso compounds are a causative factor in human cancer is not conclusive. [41,42] However, the genotoxic burden to patients resulting from nitrosation of drug substances containing secondary or tertiary amine groups may well be higher than that from preformed genotoxic impurities.…”
Section: Endogenous Formation Of Genotoxinsmentioning
confidence: 99%